Does uncertainty affect non-response to the European Central Bank's survey of professional forecasters? - Víctor López-Pérez (Kiel Institute for the World Economy (IfW), 2016)
This paper explores how changes in macroeconomic uncertainty have affected the decision to reply to the European Central Bank's Survey of Professional Forecasters (ECB's SPF). The results suggest that higher (lower) aggregate uncertainty increases (reduces) non-response to the survey. This effect is statistically and economically significant. Therefore, the assumption that individual ECB's SPF data are missing at random may not be appropriate. Moreover, the forecasters that perceive more individual uncertainty seem to have a lower likelihood of replying to the survey. Consequently, measures of uncertainty computed from individual ECB's SPF data could be biased downwards.
Keywords: D81; D84; E66; 330; Non-response; uncertainty; Survey of Professional Forecasters; European Central Bank